IMPLEMENTASI UU NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA TERKAIT PEREDARAN CD MUSIK BAJAKAN DI WILAYAH KABUPATEN BULELENG - Gede Agus Wahyu Dana; Dewa Gede Sudika Mangku; Ketut Sudiatmaka (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2020)
This study aims to find out how the implementation of Law number 28 of 2014 concerning copyright related to the still circulation of pirated music CD (compact disk) in the district of Buleleng and to find out the efforts made by the local government especiallythe police with the discovery of pirated music CD. This research is an empirical research that is descriptive in nature. Data collection using library research, observation, and interviews. Samples were taken from pirated CD sellers and pirated CD consumers and the police using proposive sampling techniques. Data analysis was performed with a qualitative descriptive analysis and presented in a descriptive analysis. Research results show that where Law number 28 of 2014 concerning copyright has not been implemented properly in society, the lack of complaints from creators and the public and the legal culture of society is still relatively weak. The efforts made by the local government are only preventive and repressive (investigative) action if there is chaos in the community.